Effectiveness of Project-Based Online Learning on 21st Century Thinking Skills of Indonesian Students: A Meta-Analysis Research from 2018-2023 - Jonni Mardizal; Wiwid Suryono; Kartika Nuswantara; Arniati Muhe; Komari (Jurnal Penelitian Pendidikan IPA, 2023)
Online learning plays an important role in supporting learning activities between students and teachers. However, there has been no quantitative meta-analysis of the overall effectiveness of Project-Based Learning online-based learning on students' 21st century thinking skills. The purpose of the study was to investigate the effectiveness of project-based learning online learning on the thinking skills of 21st century students in Indonesia.Â  This type of research is a meta-analysis. The meta-analysis analyzed 16 articles published from 201 8-2023. The results of the analysis concluded that project-based online learning has a significant effect on students' 21st century thinking skills with a summary effect or mean effect size (rE = 1.04 High criteria). Furthermore, these findings conclude that the project-based online learning model effectively encourages students' 21st century thinking skills compared to conventional learning models.